Getting EFL Learners to Speak: Obstacles and Solutions - Eulis Rahmawati (Loquen, 2017)
This research investigates how process of speaking instruction takes place at IAIN SMH Banten. There are three main issues in the research problems: the process of teaching speaking, obstacles found in the teaching and learning process, and what efforts do they make to solve the obstacles in speaking. The process of teaching speaking discusses materials, preparation, procedures or steps in teaching speaking while obstacles and solutions discuss the speaking barriers that the students faced in speaking class and how they minimize the barriers. By applying descriptive qualitative research design to students of fourth semester in academic year 2014/2015, the result shows that the focus of speaking instruction at the fourth semester of English education department of IAIN SMH Banten seemed to let the students speak, without any language skills discussion as the feedback. At the same time, during the process of speaking instruction there are some problems faced by students. The first is problem of limited English Competence dealt with students poor of vocabulary and the second is problems of psychological factors.